Аналіз методів оцінювання ефективності ІТ-проєктів впровадження систем віртуальної реальності у театрах - Васильцова, Н. В. (ХНУРЕ, 2025)
The analysis conducted in this paper has shown that the implementation of ІТ projects for developing and implementing virtual realІТy (VR) systems in theater activІТies differs significantly from classical approaches to project management in the ІТ industry. The effectiveness of implementing VR projects in theaters is evaluated using various financial, technical, and user metrics. An integrated approach is proposed that uses tradІТional financial methods based on analytical tools and modern machine learning methods to predict and analyze the behavioral data of VR system users.
Keywords: метод оцінювання; іт-проєкт; віртуальна реальність; театр